Distributed education using the mStar environment - Synnes, Kåre; Lachapelle, Serge; Parnes, Peter; Schefström, Dick (Luleå tekniska universitet, Datavetenskap, 1997)
The mStar environment for distributed education utilizes the WWW and IP-multicast to enable teacher-student collaboration over large geographic distances. Several educational projects, spanning from secondary school courses to company internal training, have deployed the mStar environment. This paper reports on experiences gained over a year of practice at the Luleå University of Technology and the Centre for distance-spanning Technology. The paper presents the methodology and technology used, while recognizing usage scenarios such as preparation of presentation material, distributed presentations, asynchronous playback of recorded and edited material, and virtual meetings for educational support. Godkänd; 1997; 20071017 (margjo)